Isolation and characterization of microcrystalline cellulose from tangkit pineapple leaves (ACT-MCC) as a pharmaceutical excipient - Astuti, Novia Tri; Efendi, M. Rifqi; Sadli, Nurul Kamilah; Pondawinata, Marizki; Ladianti, Cintasa Nabila; Apriani, Ela (Proceedings Academic Universitas Jambi, 2025)
Background: Microcrystalline cellulose (MCC) is a widely used pharmaceutical excipient due to its high compressibility, stability, and inertness in tablet formulations. Tangkit pineapple leaves (Ananas comosus), an abundant agricultural waste in Jambi, Indonesia, offer a sustainable alternative source for cellulose. Objective: This study reports the preparation and characterization of microcrystalline cellulose (ACT-MCC) derived from Tangkit pineapple leaves, as well as its physicochemical characteristics in comparison to the commercial standard, Avicel PH 102. Methods: MCC was prepared from α-cellulose isolated from dried Tangkit pineapple leaves through sequential alkali treatment, bleaching, and acid hydrolysis. Results: From 200 g of dried raw material, 19.41% (w/w) α-cellulose was obtained, which was then converted to 75% (w/w) MCC, equivalent to 14.56% of the starting material. The resulting ACT-MCC had a melting point of 247-250°C, slightly lower than Avicel PH 102 (268-270 °C). Physicochemical analysis showed a pH of 7.51, total ash 0.318% (w/w), moisture 3.13% (w/w), and drying loss of 3.42% (w/w), all within pharmacopeial limits. ACT-MCC was comparatively fine, odourless, tasteless, and yellowish in appearance. Conclusion: ATC-MCC demonstrated comparable characteristics to commercial MCC, indicating its potential usage as a locally derived pharmaceutical excipient.